Short monolithic columns for purification and fractionation of peptide samples for matrix-assisted laser desorption/ionization time-of-flight/time-of-flight mass spectrometry analysis in proteomics - Moravcová, Dana; Kahle, Vladislav; Rehulková, Helena; Chmelík, Jan; Rehulka, Pavel (Journal of chromatography. A, 2009)
This study records a novel application of methacrylate-based monolithic columns for MALDI-TOF/TOF MS analyses in proteomics for pre-concentration and separation of peptides derived from protein digestion. Reversed-phase monolithic capillary columns (30mm x 0.32mm i.d.) were created inside the fused silica capillary via thermal-initiated free-radical polymerization of ethylene glycol dimethacrylate and lauryl methacrylate monomers in the presence of 1-propanol and 1,4-butandiol as a porogen system. The elution of peptides was achieved using a linear gradient of acetonitrile from 0 to 60% in water with 0.1% trifluoroacetic acid formed in a microsyringe. Individual fractions of separated peptides were collected on the MALDI target spots covered with alpha-cyano-4-hydroxycinnamic acid used as a matrix and then they were analyzed using MALDI-TOF/TOF mass spectrometry. The developed method was tested with a mixture of tryptic peptides from bovine serum albumin and its applicability was also tested for tryptic in-gel digests from barley grain extracts of water soluble proteins separated using SDS gel electrophoresis. The number of detected peptides was approximately three to four times higher compared to the analysis without previous separation. These results show an improved quality of sample information with the higher amount of identified peptides which increased protein sequence coverage and improved sensitivity of mass spectrometry measurements.
Keywords: elektroforéza v polyakrylamidovém gelu; sérový albumin hovězí; Reproducibility of Results; oxid křemičitý; proteomika; reprodukovatelnost výsledků; methakryláty; Serum Albumin, Bovine; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Methacrylates; Hordeum; skot; ječmen (rod); Peptides; Electrophoresis, Polyacrylamide Gel; Proteomics; zvířata; Silicon Dioxide; chromatografie kapalinová; Cattle; peptidy; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Edible Grain; Chromatography, Liquid; jedlá semena; Animals